2-D porous Ni3N–Co3N hybrids derived from ZIF-67/Ni(OH)2 sheets as a magnetically separable catalyst for hydrogenation reactions. Issue 79 (3rd September 2018) - Zhang, Lin; Wu, Aiping; Tian, Mei; Xiao, Yinglu; Shi, Xia; Yan, Haijing; Tian, Chungui; Fu, Honggang
Abstract : The synergistic nitridation of Ni(OH)2 and ZIF-67 during the treatment of ZIF-67/Ni(OH)2 sheets is demonstrated to be important to forming 2-D porous Ni3 N–Co3 N hybrids that can be used as a magnetically separable catalyst for hydrogenation reactions. Abstract : 2-D porous Ni3 N–Co3 N hybrids were prepared by initial controllable growth of ZIF-67 on Ni(OH)2 sheets followed by nitridation. The synergistic nitridation of Ni(OH)2 and ZIF-67, is demonstrated to be important for the formation of 2-D porous hybrids that can be used as a magnetically separable catalyst for hydrogenation reactions.